Gender disparity in academic performance in higher education institutions: a case of Wollo University, Ethiopia - Eshetu, Amogne Asfaw; Alemu, Simret; Mulat, Aster; Abdu, Aminat; Gobezie, Bezawit; Muluken, Enatnesh; Anagaw, Asemach; Mulugeta, Elsabet; Hailemariam, Ehite; Aragaw, Sewasew (Frontiers in Education, 2024)
IntroductionGender disparity in academic achievement in developing countries is a pervasive issue that requires attention. Examining the gender gap provides empirical evidence for decision-makers. This study explored gender-based disparities in academic achievement in higher education institutions.MethodsWe employed an ex-post facto research design and analyzed the cumulative grade point average (CGPA) and national exit examination results of 1,323 students to attain the study objective. Data analysis was conducted using the Chi-square test, independent samples t-test, correlation, and simple linear regression tests.ResultsThe results revealed a statistically significant underrepresentation of female students in the top-achieving groups (χ2 (1) = 7.929, p < 0.05), whereas their proportion in the lower-achieving groups (χ2 (1) = 19.18, p < 0.05) was higher than expected. Additionally, a significantly more significant proportion of female students scored below the 50% minimum passing mark on the national exit examination (χ2 (1) = 23.857, p < 0.05). Furthermore, the analysis demonstrated that male students attained statistically and significantly higher marks on both their CGPA [t (1231) = 6.432, p < 0.001] and national exit examination [t (1231) =10.855, p < 0.001] at a 95% level of significance. The correlation test results revealed that students who performed well academically in their CGPA were more likely to score higher on the national exit examination [r (1323) =0.525, p < 0.01].DiscussionThe findings suggest that further research is necessary to explore the underlying factors contributing to the observed gender disparities in academic achievement at the tertiary level. Moreover, additional efforts have to be undertaken by concerned bodies to support and mentor female students at higher institutions.